Life after power : seven presidents and their search for purpose beyond the White House - Cohen, Jared, 1981- (Simon & Schuster, 2024)
From the Founding to today, this book tells the stories of seven former presidents who each changed history and offered lessons about how to decide what to do in the next chapter of life as they handled human problems of ego, finances and questions about their legacy and mortality.